From interventionist imaging to intraoperative guidance: New perspectives by combining advanced tools and navigation with radio-guided surgery De la imagen intervencionista a la guía intraoperatoria: nuevas perspectivas combinando herramientas avanzadas y navegación con la cirugía radioguiada - Vidal-Sicart, Sergi; Olmos, R. Valdes; Nieweg, O. E.; Faccini, R.; Grootendorst, M. R.; Wester, H. J.; Navab, N.; Vojnovic, Borivoj; Van Der Poel, H.; Martinez-Roman, S.; Klode, Joachim; Wawroschek, F.; et al. (Revista Espanola de Medicina Nuclear e Imagen Molecular, 2018)
The integration of medical imaging technologies into diagnostic and therapeutic approaches can provide a preoperative insight into both anatomical (e.g. using computed tomography, magnetic resonance imaging, or ultrasound), as well as functional aspects (e.g. using single photon emission computed tomography, positron emission tomography, lymphoscintigraphy, or optical imaging). Moreover, some imaging modalities are also used in an interventional setting (e.g. computed tomography, ultrasound, gamma or optical imaging) where they provide the surgeon with real-time information during the procedure. Various tools and approaches for image-guided navigation in cancer surgery are becoming feasible today. With the development of new tracers and portable imaging devices, these advances will reinforce the role of interventional molecular imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Molecular imaging; Optical image; Radioguided surgery; Sentinel node